Is a freeze-all policy the optimal solution to circumvent the effect of late follicular elevated progesterone? A multicentric matched-control retrospective study analysing cumulative live birth rate in 942 non-elective freeze-all cycles. Issue 9 (5th July 2021) - Racca, A; Vanni, V S; Somigliana, E; Reschini, M; Viganò, P; Santos-Ribeiro, S; Drakopoulos, P; Tournaye, H; Verheyen, G; Papaleo, E; Candiani, M; Blockeel, C
Abstract: STUDY QUESTION: Is late follicular elevated progesterone (LFEP) in the fresh cycle hindering cumulative live birth rates (CLBRs) when a freeze only strategy is applied? SUMMARY ANSWER: LFEP in the fresh cycle does not affect the CLBR of the frozen transfers in a freeze only approach, nor the embryo freezing rate. WHAT IS KNOWN ALREADY: Ovarian stimulation promotes the production of progesterone (P) which has been demonstrated to have a deleterious effect on IVF outcomes. While there is robust evidence that this elevation produces impaired endometrial receptivity, the impact on embryo quality remains a matter of debate. In particular, previous studies have shown that LFEP is associated with a hindered CLBR. However, most clinical insight on the effect of progesterone on embryo quality in terms of CLBRs have focused on embryo transfers performed after the fresh transfer, thus excluding the first embryo of the cohort. To be really informative on the possible detrimental effects of LFEP, evidence should be derived from freeze-all cycles where no fresh embryo transfer is performed in the presence of progesterone elevation, and the entire cohort of embryos is cryopreserved. STUDY DESIGN, SIZE, DURATION: This was a matched case-control, multicentre (three centres), retrospective analysis including all GnRH antagonist ICSI cycles in which a freeze all (FA) policy of embryos on day 3/5/6 of embryonic development was applied between 2012 and 2018. A total of 942 patients (471 cases with elevated P and 471 matched controls with normal P values) were included in the analysis. Each patient was included only once. PARTICIPANTS/MATERIALS, SETTING, METHODS: The sample was divided according to the following P levels on the day of ovulation triggering: <1.50 ng/ml and ≥1.50 ng/ml. The matching of the controls was performed according to age (±1 year) and number of oocytes retrieved (±10%). The main outcome was CLBR defined as a live-born delivery after 24 weeks of gestation. MAIN RESULTS AND THE ROLE OF CHANCE: The baseline characteristics of the two groups were similar. Estradiol levels on the day of trigger were significantly higher in the elevated P group. There was no significant difference in terms of fertilisation rate between the two groups. The elevated P group had significantly more cleavage stage frozen embryos compared to the normal P group while the total number of cryopreserved blastocyst stage embryos was the same. The CLBR did not differ between the two study groups (29.3% and 28.2% in the normal versus LFEP respectively, P = 0.773), also following confounder adjustment using multivariable GEE regression analysis (accounting for age at oocyte retrieval, total dose of FSH, progesterone levels on the day of ovulation trigger, day of freezing, at least one top-quality embryo transferred and number of previous IVF cycles, as the independent variables). LIMITATIONS, REASONS FOR CAUTION: This is a multicentre observational study based on a retrospective data analysis. Better extrapolation of the results could be validated by performing a prospective analysis. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study demonstrating that LFEP in the fresh cycle does not hinder CLBR of the subsequent frozen cycles in a FA approach. Thus, a FA strategy circumvents the issue of elevated P in the late follicular phase. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for this study. Throughout the study period and manuscript preparation, authors were supported by departmental funds from: Centre for Reproductive Medicine, Brussels, Belgium; Infertility Unit, Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico, Milan, Italy; Centro Scienze Natalità, San Raffaele Scientific Institute, Milan, Italy; and IVI-RMA, Lisbon, Portugal. E.S. has competing interests with Ferring, Merck-Serono, Theramex and Gedeon-Richter outside the submitted work. E.P. reports grants from Ferring, grants and personal fees from Merck-Serono, grants and personal fees from MSD and grants from IBSA outside the submitted work. All the other authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.